Penyuluhan Hukum Teknologi Informasi Bagi Siswa Dalam Upaya Meningkatkan Literasi Digital Dan Kesadaran Hukum - Ilham Aji Pangestu; Sunarya Sunarya; Muhammad Rizqi Fadhlillah (Pusat Riset dan Inovasi Nasional, 2025)
The development of information and communication technology has brought significant changes to the lives of teenagers, especially high school students as active users of digital media. On the one hand, technology opens up opportunities for creativity and productivity, but on the other hand, it also increases the risk of technological misuse with legal implications, such as cyberbullying, the spread of hoaxes, data privacy violations, and other cybercrimes. This community service activity aims to increase students' understanding and legal awareness of the safe, ethical, and lawful use of information technology. The method used is legal counselling through material presentation, discussion, and question and answer sessions with students participating in the School Environment Introduction Period (MPLS) at Dharma Putra High School. The results of this community service activity emphasised the implementation process and the students' initial response to the information technology legal education material. In general, the outreach activity ran smoothly and received a participatory response from students. This was reflected in the students' involvement in the discussion and question and answer sessions, where students actively asked questions and expressed their views on the use of social media, digital ethics, and legal risks in daily digital activities. These interactions showed the students' interest and concern for legal and information technology issues.